Stakeholder integration in service innovation - An exploratory case study in the healthcare industry - Jonas, Julia; Roth, Angela (International Journal of Technology Management, 2017)
This paper explores the integration of internal and external stakeholders in service innovation. Building upon the co-creative paradigm, the resource and knowledge integration of stakeholders in dynamic and complex service systems is gaining importance. This case study analyses the practice of stakeholder integration in a service innovation project at a German provider for medical appliances. We show that stakeholder integration is realised in the modes of reactive integration for the majority of stakeholders, whereas mutual integration is realised with members of the organisation, only. Customers are integrated as reactive resources throughout the innovation process, also informally and indirectly. The evidence from this empirical study suggests that stakeholder integration in service systems creates interdependencies between stakeholders and implicates that indirect ways of stakeholder integration have to be taken into account for project and stakeholder management.
Created from Fastlane, Scopus look-up
Keywords: Case study research; Healthcare industry; Indirect integration; Modes of integration; Service innovation; Service systems; Stakeholder integration